Politeness Utterances in English Discussion - Elia Sapitri; . Prihantoro; Sarwo Edy; Jumatul Hidayah (IAIN Syekh Nurjati Cirebon, 2020)
Abstract: This study was conducted to investigate the types of maxims according to the principles of politeness as used by tertiary English students in the context of semi-formal discussion. This study used a descriptive qualitative method. 20 intermediate tertiary English students from one of the universities in Bengkulu were involved as the participants of this study. They were selected using a purposive sampling technique. The findings revealed that in the context of semi-formal English discussion, there were four types of maxims representing politeness. They ranged from tact maxim, generosity maxim, approbation maxim, to agreement maxim. Those maxims were realized into several uses of utterances such as requesting, asking, offering, responding, and answering. This study supports a premise that the uses of politeness maxims in English communication contribute to the success of communication per se.